Modelagem geográfica de limites municipais - estudo de caso: Nova Lima e Belo Horizonte - MG - Andre Ferreira Borges (2014)
Currently the techniques of remote sensing, GIS and spatial data modeling are essential instruments for planning in all spheres of government. However, even with the advent of these technologies for mapping, in Brazil there is no application, standardization or well defined line of action concerning conflicts, inaccuracies and compatibility of all municipal limits, since many were described for the last time on the 1950s. It also occurs the difficulty related to de-characterization of various landforms existing in times of existing laws as a result of urbanization, mining and other factors that modify the geographical landscape. These indeterminacies refer to cartographic production generated in different types of Geodetic Systems, which can cause distortions in the resulting products and the resulting analyses, if improperly processed or if wrongly interpreted. In this context, the present study aims to identify factors that hinder the demarcation of municipal borders, providing a temporal analysis of geographical landscape changes and proposing a methodology to delimitate territorial limits through exchanges between municipalities. The study area comprises the boundary between the municipalities of Nova Lima and Belo Horizonte, specifically between the neighborhoods of Vila da Serra (municipality of Nova Lima) and Belvedere (municipality of Belo Horizonte). The methodology developed through remote sensing and geoprocessing tools includes georeferencing of historical maps, thematic maps construction and evaluation of conflicts of interest. Through analogies of geodetic techniques incompatibilities between the geodetic reference systems were verified. At the end, the urbanistic parameters of the conflict areas, relevant legislation and economic issues were observed. In conclusion, the paper presents a methodology for the remodeling of the municipal boundaries. Through the results, it is identified that the delimitation of municipal boundaries cannot be grounded only for cartographic issues, these changes must be arising from analyzes involving multidisciplinary teams.